SAP Fiori Design Overview - Deepak Kumar (North American Journal of Engineering Research, 2023)
SAP Fiori is a design language that aims to improve user experiences, for business applications built on SAP User Experience. Launched in 2013 SAP Fiori transforms how users engage with SAP software by focusing on simplicity, efficiency, and user design principles. It includes a range of apps for business tasks such as approving work requests handling transactions running calculations and managing self-service activities. The main objective of SAP Fiori is to provide a seamless user experience across devices like computers, tablets, and smartphones. Integrated into the SAPUI5 front-end library this framework offers more than 170 UI controls and multiple layout options to ensure consistency in design, control behavior, and visual appearance. While the framework itself doesn't guarantee a user experience, adherence to the SAP Fiori guidelines is crucial for achieving this goal. These guidelines focus on creating layouts that are user-friendly and easy to maintain while maintaining a look through consistent interaction patterns. They promote a user-centered approach that helps UX designers and developers align their designs, with SAP UI5 controls. By leveraging built components (SAP UI5 components) application development can be accelerated significantly. The SAP Fiori design brings a range of benefits, like themes, smart home pages, and an interactive chat experience all aimed at improving how users interact with the system. Moreover, SAP Fiori makes use of up-to-date web technologies such, as HTML5, CSS3, and JavaScript to guarantee speedy performance. It also works seamlessly with SAP S/4HANA, the ERP suite making business operations more straightforward and facilitating decision-making in real-time.